2015 Computing in Cardiology Conference (CinC) 2015
DOI: 10.1109/cic.2015.7408639
|View full text |Cite
|
Sign up to set email alerts
|

The PhysioNet/Computing in Cardiology Challenge 2015: Reducing false arrhythmia alarms in the ICU

Abstract: High false alarm rates in the ICU decrease quality of care by slowing staff response times while increasing patient delirium through noise pollution. The 2015 Physio-Net/Computing in Cardiology Challenge provides a set of 1,250 multi-parameter ICU data segments associated with critical arrhythmia alarms, and challenges the general research community to address the issue of false alarm suppression using all available signals. Each data segment was 5 minutes long (for real time analysis), ending at the time of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(186 citation statements)
references
References 10 publications
1
183
0
2
Order By: Relevance
“…In order to detect the pulse from the ABP and PPG signals, we used the open-source ABP pulse detection algorithm which is available in PhysioNet [6]. Since, ECG channels in the training set showed that the available ECG signals existing various disturbances such as clipping of the QRS complexes, and other noises, beats detected should be accomplished from different channels and signals and then compared them with each other.…”
Section: Quality Assessments For Pulsatile and Ecg Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to detect the pulse from the ABP and PPG signals, we used the open-source ABP pulse detection algorithm which is available in PhysioNet [6]. Since, ECG channels in the training set showed that the available ECG signals existing various disturbances such as clipping of the QRS complexes, and other noises, beats detected should be accomplished from different channels and signals and then compared them with each other.…”
Section: Quality Assessments For Pulsatile and Ecg Signalmentioning
confidence: 99%
“…In this section of algorithm, we focused on 5 life threatening arrhythmias, namely extreme tachycardia (ETC), ventricular fibrillation or flutter (VFB), asystole (ASY), extreme bradycardia (EBR), or ventricular tachycardia (VTA) and based on the clinical definition and different characteristics of each of them, signal quality features are used for them [6]. In our algorithm, the heuristic thresholding of each ABP pulse are computed with the function of abpfeature, and also, since blood pressure variation can occur during asystole and ventricular tachycardia, these features can detect these abnormalities accurately.…”
Section: Heart Beat Detection and Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computing For our analysis on ECG SQIs we used the ECG signals in the CinC 2015 training set [5]. We focused our analysis on asystole, bradycardia, and tachycardia records since ventricular tachycardia and ventricular fibrillation/flutter result in extreme modification of the ECG waveform.…”
Section: Datasetmentioning
confidence: 99%
“…Similar approaches can be used in automatic algorithms to reduce false alarms. For example, the Computing in Cardiology (CinC) 2015 challenge focused specifically on reducing false arrhythmia alarms in the ICU using patient monitoring algorithms which use multimodal physiological waveforms [5]. However combining information from multiple physiological signals introduces a new potential risk of adding noise artifacts from a low quality signal onto information from a high quality signal (e.g.…”
Section: Introductionmentioning
confidence: 99%